2022
DOI: 10.1002/vms3.1043
|View full text |Cite
|
Sign up to set email alerts
|

The effect of acidifier supplementation on egg production performance and intestinal histology of Japanese quail (Coturnix japonica)

Abstract: Background Acidifier are substances with antibacterial, antifungal, antimicrobial, performance and health benefits that are frequently employed in feed acidification, especially in poultry diet. Meanwhile, the most important factor for acidifier efficiency is the proportion of different acids in the final product. Objectives This study aimed to investigate the effect of dietary supplementation of a commercial acidifier on egg production and histology of the small intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
1
2
0
Order By: Relevance
“…When compared to the control (T 0 ) and antibiotic (T 3 ) groups, broilers fed with acidifiers and probiotics (T 1 and T 2 ) showed greater gains in body weight and increased feed conversion ratios. This is in line with the body of research showing that acidifiers and probiotics can have a good effect on the intestinal environment, nutrient uptake, and growth performance in chicken ( Aliverdi-Nasab et al., 2023 ; Leone & Ferrante, 2023 ; Mantzios et al., 2023 ; Vimon et al., 2023 ).…”
Section: Discussionsupporting
confidence: 86%
“…When compared to the control (T 0 ) and antibiotic (T 3 ) groups, broilers fed with acidifiers and probiotics (T 1 and T 2 ) showed greater gains in body weight and increased feed conversion ratios. This is in line with the body of research showing that acidifiers and probiotics can have a good effect on the intestinal environment, nutrient uptake, and growth performance in chicken ( Aliverdi-Nasab et al., 2023 ; Leone & Ferrante, 2023 ; Mantzios et al., 2023 ; Vimon et al., 2023 ).…”
Section: Discussionsupporting
confidence: 86%
“…Fouladi et al (2017) showed that quail diets supplemented with organic acid had reduced E. coli and Salmonella compared to the control group. However, Aliverdi-Nasab et al (2023) demonstrated that acidifier supplementation on quail diets did not affect total aerobic, Lactobacillus, and E. coli. Bansod et al (2020) showed that 0.25% acetic acid + 0.25% butyric acid + 0.25% propionic acid addition to quail diet significantly increased E. coli and Salmonella compared to the control group.…”
Section: Discussionmentioning
confidence: 91%
“…VH, CD, and VH/CD serve as vital indicators for measuring intestinal nutrient digestion and absorption abilities, as well as its health status [18]. The villus's edges secrete various digestive enzymes; thus, higher VH indicates stronger enzyme secretion capacity and better digestion and absorption abilities.…”
Section: Effects Of Sphingomonas On the Histological Structure Of Int...mentioning
confidence: 99%